Insane Sisters : Or, the Price Paid for Challenging a Company Town - Andrews, Gregg (Book collections on Project MUSE., 1999)
Her efforts ultimately resulted in her court-ordered confinement in 1927 to Missouri's State Hospital Number One for the Insane, where she remained until her death at age sixty-eight."--Jacket.